Using Short Message Service as An Interactive Health Education to Prevent Cardiovascular Disease - BS Bintoro (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Background: Puskesmas (Primary health care /PHC) in Indonesia is the one of the primary ....